Impaired heart rate variability in patients with arrhythmogenic cardiomyopathy: A multicenter retrospective study in China - Zhang, Baowei; Zhou, Chunjiang; Liu, Jinqiu; Zhang, Jinlin; Jiang, Chenyang; Tang, Min; Xie, Jiaxi; Wu, Yizhang; Xie, Xin; Li, Xiaorong; Yu, Jinbo; Wang, Xuecheng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac sympathetic nerve system (SNS) might play an important role in arrhythmogenesis of arrhythmogenic cardiomyopathy (ACM). This study aims to assess the activity of cardiac SNS in ACM patients by heart rate variability (HRV), and to investigate its predictive value for sustained ventricular tachycardia (sVT). Methods A total of 88 ACM patients and 65 sex- and age- matched healthy participants were enrolled. The time domain measures were used to evaluate the activity of cardiac SNS. An independent cohort with 48 ACM patients was as the validation cohort. Results ACM patients had lower levels of standard deviation of all NN intervals (SDNN) [118.0 (90.3, 136.8) vs. 152.0 (132.5, 174.5) ms, p < 0.001] compared with healthy participants. Further analysis showed ACM patients with sVT had lower levels of SDNN than those without sVT (105.0 ± 28.1 vs. 131.8 ± 33.1 ms, p < 0.001). Multivariate logistic regression analysis showed SDNN was independently associated with sVT in ACM patients [odds ratio (OR) 0.59, 95% confidence interval (CI) (0.45–0.78), p < 0.001]. Receiver operating characteristics curve demonstrated SDNN had clinical values in predicting sVT in ACM patients [area under the curve (AUC) = 0.73, 95% CI (0.63–0.84), p < 0.001], which was verified in the validation cohort. Conclusion The present study suggests that HRV is impaired in patients with ACM, and the SDNN level has a moderate value in risk stratification for sVT in ACM patients. In addition, the finding might provide new target for the further management of ACM with integrated traditional Chinese and western medicine.